Desain Pengembangan E-Modul IPAS Terintegrasi Educaplay pada Siswa Kelas III Sekolah Dasar - Wikut Deniarti; Sekar Purbarini Kawuryan; Fery Muhamad Firdaus (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study deeply explores the development phase in creating an IPAS e-module integrated with Educaplay. The research is driven by the urgent need for innovative teaching materials, aiming to provide a solution for more effective and engaging learning. We adopted a Research and Development (R&D) approach, utilizing a mixed-methods design. The ADDIE model, as proposed by Branch, guided our development, consisting of five systematic stages: (1) Analyze, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. Our primary focus was specifically on the development stage. Here, we aimed to produce an initial prototype of the Educaplay-integrated IPAS e-module. This process involved conceptualizing the e-module, determining relevant IPAS content for third-grade elementary students, and seamlessly integrating Educaplay elements into its structure. The tangible outcomes of this research include a flowchart detailing the e-module's overall usage flow and a storyboard visualizing each page or section, including the placement of Educaplay activities. Both of these outputs serve as comprehensive initial designs for the Educaplay-integrated IPAS e-module, which will eventually be implemented in IPAS learning for third-grade elementary school students.